Comparison of concentric isokinetic torque peak in active individuals with and without the application of Kinesio Taping - Micheletti, Jéssica Kirsch; Souza, Sérgio Luiz Rodrigues de; Spadaccini, Ana Flávia; Junior, Rinaldo Bernardelli; Menossi, Berlis Ribeiro dos Santos (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Physically active individuals constantly seek resources that can improve their muscle performance, avoid the appearance of lesions and even relapses. Kinesio Taping has been used for both treatment/prevention of injury and to improve functional performance. The isokinetic dynamometer enables rapid quantitative analysis of many parameters of muscle function, being the peak torque the most representative in research and clinical practice. Objective: To compare the concentric peak torque isokinetic in active individuals with and without the application of kinesio taping. Method: 10 male volunteers were evaluated and submitted to the IPAQ questionnaire, where they were considered actives. Then, were realized isokinetic evaluations into steps: Phase Control (without application of elastic taping) and Phase Bandage (with application of placebo and original bandage). The same protocol isokinetic repetitions of 5 to 60 ° / s knee flexion and extension was adopted in all the stages for the reliability and reproducibility of the data. Results: The application of taping in physically active individuals in isokinetic evaluation did not increase the concentric peak torque at 60 °/s. Conclusion: Was observed reliability and reproducibility of the results, however, no significant differences were observed in concentric peak torque isokinetic of the quadriceps of active individuals with and without the application of the original kinesio taping and placebo.